Determinasi Kepuasan Pelanggan dalam Membentuk Loyalitas Literature Review Sistematis pada Tren Pemasaran Modern - Ravena Diyan Rezita; Anggun Amelia Contessa; Moelyaning Siwi; Mu’allimin Mu’allimin (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
Customer satisfaction and loyalty are central issues in marketing management, as both play crucial roles in ensuring business sustainability amid increasing competition. Satisfied customers tend to make repeat purchases, provide positive recommendations, and build long-term relationships with the company. Therefore, understanding the factors that influence customer satisfaction and loyalty has become an important agenda for both academics and practitioners. This study aims to address two main questions: (1) What factors influence customer satisfaction? and (2) How does satisfaction contribute to the formation of customer loyalty? The method used is a literature review, selecting articles from various online databases such as ResearchGate, Academia, and open-access journals using the keywords customer satisfaction and customer loyalty. Of the 45 identified articles, 20 were selected for in-depth analysis. The review results reveal three main trends: first, service and product quality are the most consistent determinants of satisfaction; second, price, promotion, and brand image play significant roles; and third, customer trust is an essential variable that strengthens the satisfaction–loyalty relationship. Overall, satisfaction functions as the main mediating variable in the formation of customer loyalty.